Organization of aerobactin, hemolysin, and antibacterial resistance genes in lactose-negative Escherichia coli strains of serotype O4 isolated from children with diarrhea. - Colonna, B (1992)
Epidemiologically related, non-lactose-fermenting (NLF) Escherichia coli strains of serotype O4 have been isolated at a high frequency from children with diarrhea in Somalia (M. Nicoletti, F. Superti, C. Conti, A. Calconi, and C. Zagaglia, J. Clin. Microbiol. 26:524-529, 1988). In order to define the virulence potential of these strains, we characterized the replication properties of their high-molecular-weight plasmids and studied the genetic locations and organization of the aerobactin (aer) and hemolysin (hly) determinants encoded by 23 NLF O4 E. coli strains. Southern blot hybridizations, mobilization assays of nonconjugative plasmids, and incompatibility-exclusion experiments conducted with a conjugative incompatibility group FI (IncFI) plasmid showed that (i) 20 out of the 23 strains examined harbor a 160- to 180-kb IncFI plasmid that shares homology with the basic replicons RepFIA, RepFIB, and (except for the plasmid of one strain) RepFIC, and 22 strains also contain a 40- to 140-kb IncFII plasmid sharing homology with the RepFIIA replicon; (ii) the IncFI plasmid is nonconjugative and carries antibiotic resistance genes; (iii) the aer system is located on the IncFI plasmids and/or the chromosomes in the three strains not harboring IncFI, and it is found in an inverted orientation; (iv) the hly determinants are located on the chromosome, and their genetic organization is well conserved and closely resembles that of the reference hemolytic plasmid pHly152; and (v) Hly- mutants obtained by transposon insertion mutagenesis are not cytotoxic to HeLa cell monolayers, indicating that hemolysin is responsible for the high cytotoxic activity we have previously reported for these strains. The structural organization of the plasmid-encoded aer operon, together with the finding that those plasmids also carry antibiotic resistance genes, indicates that the IncFI plasmid of the NLF O4 E. coli strains studied more closely resembles aer-encoding virulence IncFI Salmonella R plasmids than E. coli ColV plasmids. The data presented here cannot rule out whether the strains examined are potentially intestinal or extraintestinal pathogens. Nevertheless, the genetic organization of the virulence genes, together with the epidemiological behavior and the wide spectrum of antibiotic resistance of the NLF O4 E. coli strains, indicates that these strains are structured as typical E. coli pathogenic isolates of human origin.